Fluorite material sources and magmatic–tectonic controls in hydrothermal fluorite deposits - Fengyu Sun; Changling Qu; Xin Du; Xiujun Zhao; Yao Dong; Gaoshe Cao; Xinhang Zhou; Xiaochen Ma (PLoS ONE, 2026)
A fundamental yet unresolved issue in hydrothermal fluorite deposits is that initial 143 Nd/ 144 Nd ratios vary significantly among different veins, even among those with similar mineralization ages within the same region. This discrepancy likely reflects variations in the material sources of hydrothermal fluids, although the specific controlling factors and mechanisms remain unclear. To address this issue, this study analyses two types of fluorite veins on the southern margin of the North China Craton—both controlled by the same fault system and the same pluton—using Sm-Nd and C-O isotopes. The Baimiaogou fluorite veinlets represent conduit structures for hydrothermal migration, whereas the Yangshan fluorite veins represent host structures for ore precipitation. The results show that the Baimiaogou veinlets, which acted as fluid conduits, display highly variable isotopic compositions, with initial 143 Nd/ 144 Nd ratios of 0.511379 to 0.511757, ε Nd ( t ) values of –21.55 to –14.17, and T DM2 ages of 1.64 to 1.93 Ga. Associated calcite exhibits a pronounced oxygen isotope shift, with δ 18 O V-SMOW ‰ values between 1.6‰ and 7.0‰. In contrast, the Yangshan veins, which served as host structures, show isotopic consistency, with tightly clustered initial 143 Nd/ 144 Nd ratios (0.511751–0.511799), ε Nd ( t ) values (–14.29 to –13.36), T DM2 ages (1.58–1.60 Ga), and associated calcite δ 18 O V-SMOW ‰ values (7.5–8.5‰). Neodymium isotope mass balance calculations indicate that the variations in Nd isotope values reflect mixing between initial magmatic-hydrothermal fluids and the ancient Taihua Group metamorphic basement during fluid migration. Macro- and microstructural analyses reveal that the Baimiaogou veinlets experienced multiple tectonic pulses within an open system characterised by dynamically changing fluid flow paths, whereas the Yangshan veins formed during a single phase of large-scale extensional faulting, with fluid precipitation occurring in a relatively closed space. Thus, the nature and pulsatory behaviour of fault structures also control the variations in Nd isotope values. This model highlights the coupled control of magmatism and structural processes on the material sources of fluorite in hydrothermal deposits, providing new constraints for understanding the metallogenic mechanisms of hydrothermal fluorite systems.